Instagram Social Media Content Production Management On the @mayakorneliaa Account as a Traveler Vlogger with a Focus on Content in The Country of Nepal - Muhammad Arya Adhi Maulana; Dwi Arifianto, Budi (Jogjakarta Communication Conference (JCC), 2025)
This study analyzes the management of Instagram content production on the @mayakorneliaa account, which is independently managed by a travel vlogger with a focus on content creation in Nepal. In this phase of digital content, it is important to understand the content production strategies carried out independently. This study uses a qualitative method with a case study approach, then collects data in the form of interviews conducted via Zoom and analysis of Instagram content archives. This study refers to the POAC (Planning, Organizing, Actuating, Controlling) framework to examine each stage of the content production process. The results show that strategic planning, such as selecting destinations that are rarely covered and formulating main content themes, can increase visibility. Tools such as the DJI Pocket 3 camera were chosen for their portability and visual quality, supporting the production organization process. Content execution combines a structured rundown with spontaneous filming to capture authentic moments. Control is exercised through engagement metrics such as views, likes, and comments; one spontaneous piece of content achieved 5.3 million views, while one planned piece only received 12,000 views. This study also identified challenges faced by content creators when producing content in the target country, such as time and resource constraints. Data validity was maintained through triangulation between interview results and documentation. The conclusions of this study confirm that effective content production strategies and active audience engagement significantly contribute to the growth and engagement of independently managed travel vlogger accounts on Instagram.